From Coordination to Convergence: A Collaborative Governance Model for Multi-sectoral Stunting Reduction in Decentralized Contexts - Sapri, Sapri; Mardhatillah, Mardhatillah; Ramlan, Pratiwi (Universitas Muhammadiyah Yogyakarta, 2026)
This study seeks to develop a context-sensitive collaborative governance model to enhance multi-sectoral convergence in stunting reduction within decentralized public health systems. Despite the existence of national convergence policies in Indonesia, implementation at the district level remains fragmented due to sectoral silos, institutional ego, and limited cross-sector accountability. Drawing on a qualitative case study conducted in Sidenreng Rappang, an agriculturally productive yet nutritionally challenged district, this research employed in-depth interviews with 23 stakeholders across health, agriculture, education, social protection, and community sectors. Using thematic analysis supported by NVivo software and guided by Emerson and Nabatchi’s Collaborative Governance Regime (CGR) framework, the study identified three critical barriers: misalignment between national policy and local implementation, budget fragmentation, and the absence of shared performance indicators. Despite these constraints, informal collaboration among street-level actors emerged as a key enabler of convergence. The study proposes a governance model comprising institutional bridging forums, convergent resource mapping, and shared learning systems to integrate structural and relational mechanisms. This model offers a replicable strategy for institutionalizing multi-sector collaboration in stunting programs. The research highlights that successful convergence requires not only coordination structures but also trust, mutual incentives, and adaptive capacity. While limited to one district, the findings provide a transferable framework for other decentralized settings. Future studies should validate the model through comparative or multi-region analyses.